Implementation of personalized approach in video editing learning to improve digital competency of 21st century learners - Kuswandi, Dedi; Fadhli, Muhibuddin; Zh, Miftah Hur Rahman; Haditia, Mohamad; Sinaga, Muhammad Najmi Alwi; At Thaariq, Zahid Zufar; Ardiansyah, Arief (CAHAYA PENDIDIKAN, 2025)
This study aims to develop a learning design and evaluate the effectiveness of implementing a personalized learning approach in video editing education to enhance students' 21st-century digital competencies. The research focused on providing flexibility in the choice of video editing software to accommodate diverse hardware capabilities, ensuring inclusive participation regardless of students’ device limitations. A sample of 20 students from the Content Creator extracurricular program at Al Ulum Medan Junior High School was selected based on specific criteria, particularly the inability to install Adobe Premiere Pro due to hardware constraints. Data collection methods included pre-test and post-test assessments, surveys, and skills tests. The data were analyzed using descriptive statistics and paired t-tests to assess improvement in video editing skills after allowing students to use software suited to their devices. The findings indicated a significant improvement, with a 40% increase in mean scores from pre-test to post-test. The personalized approach not only enhanced students' technical skills but also improved motivation and engagement. The study concludes that personalized learning, through adaptive software selection, is effective in overcoming technical barriers and significantly enhances video editing competencies among junior high school students.